“Incidencia de la libertad financiera en el crecimiento económico en América Latina: un enfoque de cointegración y causalidad con datos de panel, periodo 1990-2018. - Alberca Sarango., Erica Soledad (2021)
Economic growth is a primary indicator in the economy of all countries, In Latin America although it has had considerable growth, in the last decade this is inefficient since it has gone from growing from 3-4% to 1% in 2018 which is slowing down the reduction of poverty and inequality making it a vulnerable region in the face of a complicated global context, which is why the present research arises where it will be analyzed through a conjuncture analysis of this indicator and the topic originates: Incidence of financial freedom on economic growth in Latin America: a cointegration and causality approach with panel data, period 1990-2018. Likewise, the methodology used comprises a GLS model that determines the relationship of the variables; a cointegration test to identify whether there is long-run equilibrium and a causality test. The dependent variable was economic growth and the independent variable was financial freedom, and three control variables were included. The results indicate a positive and weakly significant relationship between economic growth and financial freedom at the global level, in the PIA, PIMB, and a positive and significant relationship for the PIMA. The main conclusions of this research were that it has been proven that a higher degree of financial freedom causes a higher degree of economic growth in a country; also, for the most part, there is bidirectional causality in the variables analyzed and finally, it is recommended that it is important to provide certain benefits to banks, such as temporarily reducing the bank reserve for a maximum of 2 years, so that they can lower interest rates and thus reactivate the economy.